2021
DOI: 10.3390/w13192608
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Indicators of Extreme Changes in Snow-Dominated Streamflow Regimes, Yakima River Basin Region, USA

Abstract: Snow plays a major role in the hydrological cycle. Variations in snow duration and timing can have a negative impact on water resources. Excluding predicted changes in snowmelt rates and amounts could result in deleterious infrastructure, military mission, and asset impacts at military bases across the US. A change in snowpack can also lead to water shortages, which in turn can affect the availability of irrigation water. We performed trend analyses of air temperature, snow water equivalent (SWE) at 22 SNOTEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
(86 reference statements)
0
7
0
1
Order By: Relevance
“…However, it also bears emphasizing that maintaining fixed SNOTEL monitoring locations over very long timeframes provides a crucial sentinel function. Such long‐term SNOTEL monitoring at permanent sites has enabled clear and direct observational detection and analysis of long‐term changes in mountain snow and climate attributable to global anthropogenic climate change (e.g., Mote et al, 2018; Surfleet & Tullos, 2013; Wagner et al, 2021) or other environmental shifts, like worsening wildfire threats (Giovando & Niemann, 2022; Smoot & Gleason, 2021) reflecting historical fire suppression and fuel‐load buildup, climate change, and growing human intrusions into forest lands. The need for that sentinel function will only increase going forward.…”
Section: Snotel and Snolite Automated Stationsmentioning
confidence: 99%
“…However, it also bears emphasizing that maintaining fixed SNOTEL monitoring locations over very long timeframes provides a crucial sentinel function. Such long‐term SNOTEL monitoring at permanent sites has enabled clear and direct observational detection and analysis of long‐term changes in mountain snow and climate attributable to global anthropogenic climate change (e.g., Mote et al, 2018; Surfleet & Tullos, 2013; Wagner et al, 2021) or other environmental shifts, like worsening wildfire threats (Giovando & Niemann, 2022; Smoot & Gleason, 2021) reflecting historical fire suppression and fuel‐load buildup, climate change, and growing human intrusions into forest lands. The need for that sentinel function will only increase going forward.…”
Section: Snotel and Snolite Automated Stationsmentioning
confidence: 99%
“…Previous studies have shown dramatic declines in western United States snowpack (e.g., Mote, 2003; Mote et al., 2018) in concert with regional warming over the last century (May et al., 2018). This results in statistically significant increases in winter maximum streamflows as previously snow‐dominated basins transition toward rain‐dominated basins in winter (Wagner et al., 2021). Thus, changes in snowpack likely explain some of the observed shifts in the flow‐duration curve.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, winter warming and snow droughts may propagate into the summer streamflow droughts, which are projected to occur even more frequently in the future (Demaria et al 2016;Dierauer et al 2021;Patterson et al 2022). Thus, it is essential to understand how the timing of the winter-spring streamflow has changed over historical periods (Steward et al 2004;Hodgkins, Dudley 2006;Wagner et al 2021) and how the timing of peak flows is projected to shift in the future (Byun et al 2019).…”
Section: Introductionmentioning
confidence: 99%